Analisis Faktor Yang Mempengaruhi Brand Love Pada Produk Retail Bangunan Modern - Afifah, Bulan Millatina Basyarah (Universitas Nusa Putra, 2019)
The purpose of this study is to determine the effect of brand trust on brand love, the influence of global brand identification on brand love, the influence of self-expressive brands on brand love, and the influence of hedonic products on brand love. This research was conducted using a survey method assisted by a questionnaire distributed to respondents (consumers) of modern retail buildings located in Jakarta, Bogor, Depok, Tangerang, and Bekasi. This study uses multiple regression analysis with 216 respondents. This analysis is used to measure the strength of two or more variables and also shows the direction of the relationship between the dependent variable and the independent variable. Based on research on variables that affect brand love, as for the following conclusions, brand trust does not change brand love. The self-expressive brand has a significant effect on brand love. Hedonic products have no significant impact on brand love. Global brand identification is having a substantial impact on brand love. The self-expressive brand has a stronger influence on brand love compared to comprehensive brand identification. Companies can carry out programs that invite customers to capture activities while shopping at outlets. The company can do the making of an ad using models from abroad, and this is to maintain the image of the company.